Derivation of Peripheral Nociceptive, Mechanoreceptive, and Proprioceptive Sensory Neurons from the same Culture of Human Pluripotent Stem Cells - Saito-Diaz, Kenyi (Stem Cell Reports, 2021)
The three peripheral sensory neuron (SN) subtypes, nociceptors, mechanoreceptors, and proprioceptors, localize to dorsal root ganglia and convey sensations such as pain, temperature, pressure, and limb movement/position. Despite previous reports, to date no protocol is available allowing the generation of all three SN subtypes at high efficiency and purity from human pluripotent stem cells (hPSCs). We describe a chemically defined differentiation protocol that generates all three SN subtypes from the same starting population, as well as methods to enrich for each individual subtype. The protocol yields high efficiency and purity cultures that are electrically active and respond to specific stimuli. We describe their molecular character and maturity stage and provide evidence for their use as an axotomy model; we show disease phenotypes in hPSCs derived from patients with familial dysautonomia. Our protocol will allow the modeling of human disorders affecting SNs, the search for treatments, and the study of human development.